Karakteristik Ibu Hamil dengan Covid-19 dan Luaran Persalinannya di Rumah Sakit Kasih Ibu Surakarta - Nabila Arnest Amorita; Ira Syahriarti (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2021)
Background: Kasih Ibu Hospital as one of the referral hospitals for COVID-19 in Surakarta City, Central Java, had treated 1333 confirmed cases of COVID-19, including among them obstetric patients with COVID-19. Pregnant women are considered to be more susceptible to COVID-19 infection than those who are not pregnant and it is feared that it will result in unfavorable conditions for both mother and fetus. Until now, research on pregnant women with COVID-19 in Indonesia is still very few and limited.Objective: To provide an overview of the characteristics of maternal and neonatal outcomes at the Kasih Ibu Hospital Surakarta.Method: Data were collected from medical records of pregnant women confirmed with COVID-19 who gave birth at the Kasih Ibu Hospital, Surakarta. Data was presented in the form of a distribution based on maternal age, parity, gestational age, complication of delivery, typical complaints of COVID-19 in mothers, birth weight of infant, infant APGAR score, and infant COVID-19 status.Results and Discussion: A total of 62 pregnant women confirmed with COVID-19 gave birth at the Kasih Ibu Hospital Surakarta by sectio caesarean procedure. Of all pregnant women, most were asymptomatic and had mild symptoms, only 3.2% had moderate symptoms and no severe or critical symptoms were found. Out of 20 out of 62 babies born (32%) confirmed with COVID-19. All babies were born with good APGAR score and 4 babies were found with low birth weight, one of whom also had hypospadias.Conclusions: Further research is needed regarding the maternal-fetal transmission of COVID-19. Keywords: COVID-19; neonates; pregnancy